Expert System for Structural Optimization Exploiting Past Experience and A-priori Knowledge. - Kuntjoro, Wahyu (Cranfield University, 1994)
The availability of comprehensive Structural Optimization Systems in the market is allowing designers direct access to software tools previously the domain of the specialist. The use of Structural Optimization is particularly troublesome requiring knowledge of finite element analysis, numerical optimization algorithms, and the overall design environment. The subject of the research is the application of Expert System methodologies to support nonspecialists when using a Structural Optimization System. The specific target is to produce an Expert System as an adviser for a working structural optimization system. Three types of knowledge are required to use optimization systems effectively; that relating to setting up the structural optimization problem which is based on logical deduction; past, experience; together with run-time and results interpretation knowledge. A knowledge base which is based on the above is set, up and reasoning mechanisms incorporating case based and rule based reasoning, theory of certainty, and an object oriented approach are developed. The Expert SVstem described here concentrates on the optimization formulation aspects. It is able to set up an optimization run for the user and monitor the run-time performance. In this second mode the system is able to decide if an optimization run is likely to converge to a, solution and advice the user accordingly. The ideas and Expert System techniques presented in this thesis have been implemented in the development; of a prototype system written in C++. The prototype has been extended through the development of a user interface which is based on XView.